Flow Velocity and Field‐Aligned Current Associated With Field Line Resonance: SuperDARN Measurements. Issue 6 (29th June 2019) - Fenrich, Frances R.; Gillies, D. Megan; Donovan, Eric; Knudsen, David
Abstract: This study presents observations of the two‐dimensional velocities and field‐aligned currents of magnetospheric field line resonances. Knowledge of the two‐dimensional plasma flows is essential for determining the field‐aligned current structure of the field line resonance and for understanding the role that field line resonances play in the generation of some auroral arc forms. In this work the full velocity vectors are determined from a high‐resolution fit to the Super Dual Auroral Radar Network (SuperDARN) line‐of‐sight data. Two discrete field line resonance events are presented, one at 4.0 mHz (4‐ to 5‐min period) and the other at 0.6 mHz (30‐min period). Band‐pass filtering the north‐south and east‐west components of the total convection velocity vectors reveals the two‐dimensional velocity field specific to an individual field line resonance. The field line resonance velocities exhibit periodic vorticity, which correspond to periodic poleward moving bands of enhanced field‐aligned current. Assuming a constant ionospheric Pedersen conductance of 10 S, peak field‐aligned current values are estimated to be 2–4 μA/m 2 . The field‐aligned currents alternate between upward and downward directed and peak in magnitude ~0.5–1° poleward and/or equatorward of the peak in field line resonance flow velocity. A Swarm satellite overpass occurs directly over the 0.6‐mHz field line resonance. The SuperDARN field‐aligned current profile along the Swarm trajectory is found to be similar in magnitude and structure to that determined from Swarm‐A and Swarm‐C in situ measurements. Key Points: Two‐dimensional velocities of a field line resonance are determined from a high‐resolution fit to SuperDARN line‐of‐sight observations Field line resonance flows exhibit periodic variations in vorticity, which generate periodic poleward propagating field‐aligned currents Estimates of field‐aligned currents generated by the field line resonance are consistent with Swarm measurements of field‐aligned current